Changes of the tropical glaciers throughout Peru between 2000 and 2016 – mass balance and area fluctuations - Seehaus, Thorsten (2019)
Filiación institucional de autor: Alejo Cochachín Rapre /Autoridad Nacional del Agua - Unidad de Glaciología y Recursos Hídricos (ANA-UGRH), Huaraz, Peru